2009
DOI: 10.1152/ajpheart.00543.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vasodilator responses to sodium nitrite are mediated by an allopurinol-sensitive mechanism in the rat

Abstract: PJ. Pulmonary vasodilator responses to sodium nitrite are mediated by an allopurinol-sensitive mechanism in the rat. Am J Physiol Heart Circ Physiol 296: H524 -H533, 2009. First published December 12, 2008 doi:10.1152/ajpheart.00543.2008.-Recent studies show that pulmonary vasodilator responses to nitrite are enhanced by hypoxia. However, the mechanism by which nitrite is converted to vasoactive nitric oxide (NO) is uncertain. In the present study, intravenous injections of sodium nitrite decreased pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 27 publications
(49 reference statements)
7
56
1
Order By: Relevance
“…The results of the present study show that vasodilator responses to sodium nitrite are inhibited by cyanamide. These data suggest that both XOR and ALDH2 can act to reduce nitrite to vasoactive NO in the rat (7,20,40).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The results of the present study show that vasodilator responses to sodium nitrite are inhibited by cyanamide. These data suggest that both XOR and ALDH2 can act to reduce nitrite to vasoactive NO in the rat (7,20,40).…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism by which nitrite is reduced to NO in the rat is uncertain, but the reduction of inorganic nitrite to NO can be mediated by enzymatic mechanisms and by nonenzymatic disproportionation at low pH (12,13,16,19,22,27,35). Moreover, it has also been reported that vasodilator responses to sodium nitrite can be attenuated by allopurinol, suggesting that XOR can play a role in bioactivation of nitrite (7,20,40). The results of the present study show that vasodilator responses to sodium nitrite are inhibited by cyanamide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations